Analisa Pertimbangan Hakim Terhadap Gugatan Salah Objek Dalam Perkara Perdata No 19/Pdt.G/2020/PN Msh - Kristin Atihuta; Merry Tjoanda; Pieter Radjawane (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Civil lawsuits can meet the formal and material requirements that will be submitted to the court so that no formal or material defects are found in the lawsuit. Purposes of the Research: The purpose of this article is to find and analyze how the legal consequences of a formal or material defect in a lawsuit and judges consideration about wrong object lawsuit in the land rights disputes in a court Methods of the Research: The research method used is normative judicial with a statutory approach and conceptual approach and Sources of research legal materials include primary, secondary, tertiary legal sources. Data collection techniques in the form of literature study. Processing and analysis of legal materials used in writing is using qualitative analysis method.Results of the Research: The result of this research is that there is a formal defect in the Plaintiff's lawsuit based on the facts in the case examination in court. The Plaintiff cannot prove the argument of his lawsuit because there are differences in the object of the land dispute being sued in this case. Therefore, in filing a good and correct land dispute claim, it must meet the formal and material requirements that have become the basis of a civil lawsuit. with the consideration that the case is unacceptable.